Two Stage Lasso in Principal Component Analysis With an Application - Afraa A. Hamada (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This paper will employ a novel approach that builds upon the lasso method, utilizing it in two stages. The first stage applies to the principal components to select the important principal component and exclude the unimportant ones. This technique is effective in identifying significant principal components while attempting to eliminate bias in selecting these components over others. Additionally, it removes the ranking in determining the principal components compared to classical methods. Moreover, the second stage involves determining the effective importance within each component by zeroing out the scores loading values within each component. To compare the performance of the proposed method in principal component analysis, a simulation approach can be used. Subsequently, the performance of the proposed method is tested using real data.